Pregnant Women's Behavior in Stimulating the Fetus After Giving Education Through Audiovisual Media - Sri Setiasih; Titi Mursiti; Rozikhan Rozikhan (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
National data from the Ministry of Health of the Republic of Indonesia in 2018, 11 percent of toddlers in Indonesia experience growth and development disorders. It is estimated that 1-3 percent experience delays in motor development. Efforts to maintain and increase intelligence potential during pregnancy are very important to prepare quality Indonesian human resources in an effort to increase the Human Development Index (IPM) of Indonesian society in the future. The purpose of this study is to ascertain how fetal stimulation knowledge and behavior among pregnant women in the Bandengan Subdistrict are related to education through audiovisual media. The research design is a quasi-experiment with a one-group pretest and posttest design technique. This research was conducted in Bandengan Village, Kendal District, Kendal Regency in September-December 2022. The population in this study were all pregnant women who were in Bandengan Village Trimesters 2 and 3 in October-December 2021, with a total of 73 pregnant women. In this study, the respondents were the total population of pregnant women in Bandengan village. The measurement tool used a questionnaire regarding the depth of fetal stimulation knowledge. The result of a statistical test using the Wilcoxon test show that there is a relationship between fetal stimulation in pregnant women through audiovisual media education with a p-value of 0.000, with a description of pregnant women's behavior regarding fetal stimulation after receiving education of 100 percent. For future researchers, other methods that are more perfect in the health education model can be used.